Bullying, harassment and sexual discrimination among ophthalmologists in Australia and New Zealand. (10th January 2021) - Meyer, Juliette A.; Troutbeck, Robyn; Oliver, Genevieve F.; Gordon, Lynn K.; Danesh‐Meyer, Helen V.
Abstract: Background: Discrimination, bullying and sexual harassment (DBSH) impact the psychological well‐being of doctors and contribute to poor health outcomes. The Royal Australian and New Zealand College of Ophthalmologists (RANZCO) commissioned independent surveys to evaluate DBSH among members/trainees. Methods: Anonymous online surveys by Best Practice Australia were undertaken in 2015 and 2018. Cross‐sectional analysis was prevalence of perceived DBSH, rates of reporting, intervention and resolution undertaken. Response rate was 50% (658/1319) in 2015 and 40% (557/1401) in 2018. In both surveys, 29% were female. This is representative of the distribution of the RANZCO members. Results: In a 2015 survey, 37.6% of respondents experienced DBSH, with prevalence being the highest for females (62.3%; N = 104 cf males 27.7%; N = 167) and trainees (49.2%; N = 61). In 2018, 49.2% of respondents reported DBSH with rates low for all forms of DBSH (22%‐29%). Sexual harassment was reported by 12% and the least discussed or reported. Respondents strategy for taking action included draw on personal support network (25‐43%), official complaints to supervisors (16‐22%), human resources (2%‐10%) and RANZCO (0%‐6%). Reasons for not taking action included fear of impact of future career options (54.1%‐60.7%), fear of victimization (35.7%‐50.4%) and afraid of not being believed (31.9%‐52.4%). Satisfactory resolution rates were 6% to 25%. A majority of respondents (77%) were positive about RANZCO initiatives. Conclusions: DBSH is commonly reported by RANZCO members with female ophthalmologists more than two times more likely to experience any one of the four behaviours, three times more likely to experience discrimination and six times for sexual harassment. Fear of compromising personal and career progression contribute to low levels of reporting.